2016
DOI: 10.1111/jfpp.12905
|View full text |Cite
|
Sign up to set email alerts
|

Hot Air Drying and Microwave-Assisted Hot Air Drying of Broccoli Stalk Slices (Brassica oleraceaL. Var.Italica)

Abstract: Drying characteristics of broccoli stalk slices under hot air drying (HA) and microwave-assisted hot air drying (MWHA) at temperatures of 40, 50 and 60C is presented. In addition, the color and shape changes of the dried sample were compared. Midilli et al. model showed a good agreement with the experimental data obtained for both drying systems. The calculated effective moisture diffusivity are varied from 2.92 3 10 28 to 7.91 3 10 28 m 2 /s under HA and 6.64 3 10 28 to 13.31 3 10 28 m 2 /s under MWHA. Less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
7
27
0
Order By: Relevance
“…It was also found that higher drying temperature resulted in larger heating energy leading to raising molecular water activity and raised D eff . The results of D eff value had a good agreement with the published values by other researchers (Ashtiani et al, ; Bhattacharya, Srivastav, & Mishra, ; Khoshtaghaza et al, ; Salim, Gariepy, & Raghavan, ; Wang, Li, et al, ).…”
Section: Resultssupporting
confidence: 86%
“…It was also found that higher drying temperature resulted in larger heating energy leading to raising molecular water activity and raised D eff . The results of D eff value had a good agreement with the published values by other researchers (Ashtiani et al, ; Bhattacharya, Srivastav, & Mishra, ; Khoshtaghaza et al, ; Salim, Gariepy, & Raghavan, ; Wang, Li, et al, ).…”
Section: Resultssupporting
confidence: 86%
“…Drying alters both physicochemical and nutritional characteristics of the agricultural crops by degrading and modifying the cellular components and promoting reactions between them, and concerted efforts are being made to modify such physicochemical changes in order to achieve a favorable result (Devahastin & Niamnuy, ). Quality of the final product depends largely on the choice of the technique: while low‐temperature processes such as freeze drying (FD) preserve most of the original characteristics of the product, high‐temperature processes such as hot air drying (HAD) destroy the squishy microstructure of plant products and degrade most of the thermolabile bioactive compounds(López et al, ; Md Salim, Gariépy, & Raghavan, ). Microwave drying (MWD), a novel dehydration technique based on electromagnetic (EM) radiation, offers a faster and more energy efficient alternative to these traditional techniques but is yet to be preferred by manufacturers for processing most of the agricultural crops because of its “destructive” effect on the food (Mandal, Mohan, & Hemalatha, ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2a,b shows that there is good fit of experimental data for both MWD and FD and HAD processes with the Midilli et al's model. In earlier studies, Midilli et al's model also provided a better representation of MWD of broccoli stalk slices,leek, apple slices, and onion slices than other thin layer drying models(Md Salim et al, 2017;Süfer, Sezer, & Demir, 2017).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Combination drying methods (MW/IR drying assisted with hot air/VC, MW and IR combination) were introduced to compensate for the aforementioned drawbacks of individual drying methods. Several studies reported that combination drying methods promote faster drying time with rapid moisture diffusion and less change in color than in HA drying (Koné et al, 2013;Zhao et al, 2013;Wojdyło et al, 2014;Wu et al, 2014;Salim et al, 2016). Freeze-drying was considered a novel drying method in which frozen food or agricultural products could be dried by the sublimation of ice (Oetjen, 2000).…”
Section: Introductionmentioning
confidence: 99%